Family Support for Increasing Exclusive Breastfeeding - Masruroh, Nur; Istianah, Nine Zainiyatul (Universitas Aisyah Pringsewu, 2019)
Nursing mothers in the process of providing Exclusive Milk need support from the closest people such as family members, friends, relatives, colleagues and from the community. The purpose of this study is to determine the effect of the level of family support for exclusive breastfeeding. This type of research is analytic with a case control approach, a sample of 170 respondents of breastfeeding mothers who have babies aged more than 6 months were taken using a cluster random sampling technique. The results showed that in the case group as many as 85 nursing mothers most (57.1%) received good family support and almost half (33.3%) received less support from the family. Then in the control group as many as 85 breastfeeding mothers, almost half (42.9%) received good family support and most (66.7%) lacked support from the family. Analysis using the chi square test results that p = 0.004 which means that H0 is rejected, which means family support can increase exclusive breastfeeding. Families and communities are expected to provide support for mothers to exclusively breastfeed.ABSTRAKIbu menyusui dalam proses memberikan Air Susu Eksklusif (ASI) memerlukan dukungan dari orang terdekat seperti anggota keluarga, teman, saudara, rekan kerja maupun dari masyarakat. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh tingkat dukungan keluarga terhadap pemberian ASI Ekslusif. Jenis penelitian adalah analitik dengan pendekatan case control, sampel sebesar 170 responden ibu menyusui yang memiliki bayi usia lebih dari 6 bulan yang diambil menggunakan teknik cluster random sampling. Hasil penelitian menunjukkan bahwa dalam kelompok kasus sebanyak 85 ibu menyusui sebagian besar (57,1%) mendapatkan dukungan keluarga yang baik dan hampir setengahnya (42,9%) kurang mendapatkan dukungan dari keluarga. Kemudian pada kelompok kontrol sebanyak 85 ibu menyusui, hampir setengahnya (33,3%) mendapatkan dukungan keluarga yang baik dan sebagian besar (66,7%) kurang mendapatkan dukungan dari keluarga. Analisis menggunakan uji chi square mendapatkan hasil bahwa p= 0,004 yang berarti H0 ditolak yang artinya dukungan keluarga dapat meningkatkan pemberian ASI Eksklusif. Keluarga dan masyarakat diharapkan dapat memberikan dukungan untuk ibu dalam memberikan ASI secara eksklusif.